Analysis of the Effect of Workload, Work Life Balance, and Work Environment, on Turnover Intention with Burnout as a Mediating Variable PT SGS (Sumber Graha Sejahtera) Semarang Branch - Muhammad Farhan Afifudin; Kussudyarsana Kussudyarsana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of workload, work-life balance, and work environment on turnover intention with burnout as a mediator at PT SGS Semarang Branch. The background of this study is based on the high turnover rate at the company. This study responds to the relatively high turnover rate at PT. SGS Semarang Branch. This is evidenced by the fact that PT SGS Semarang Branch conducts employee recruitment almost every month, particularly in the production workforce sector, to enhance competencies through vocational pathways. This study employs a quantitative approach using a questionnaire method. The sample consists of 50 production department employees selected using the Slovin method. The research instrument is a questionnaire that has been validated for validity and reliability. Data analysis was assisted by the Smart PLS 4.0 program. The results of the study indicate that workload has a significant negative effect on turnover intention, work-life balance has no significant effect on turnover intention, work environment has a significant negative effect on turnover intention, burnout has a significant positive effect on turnover intention, workload has a significant positive effect on burnout, work-life balance has no effect on burnout, and work environment has no significant effect on turnover intention. Workload has a significant positive effect on turnover intention, mediated by burnout; work-life balance has no significant effect on turnover intention, mediated by burnout; and work environment has no significant effect on turnover intention, mediated by burnout.